The Role of Civil Law in the Protection of Privacy and Personal Data - Muhammad Fadly Nasution (Universitas Pahlawan Tuanku Tambusai, 2023)
In today's technological advances, electronic exchange of information and collection of personal data have become widespread and intensive, especially with the advent of the internet, social media, and various digital services. Privacy and protection of personal data have become important issues, given the risks of misuse and privacy violations that can occur. This research is qualitative in nature. The techniques used to obtain information involved careful observation and meticulous note-taking, followed by analytical procedures such as data reduction, visualisation and inference. This research aims to analyse and evaluate the effectiveness of the civil law framework in addressing the challenges faced in the digital age. The study arrived at the conclusion that in the protection of privacy and personal data, Civil Law plays an important role in providing the necessary legal foundation and framework. Through Civil Law, individuals have their privacy rights protected, obligations for parties collecting and managing personal data, the principle of informed consent, maintenance of personal data confidentiality, as well as the right of individuals to access, correct, and delete their personal data.